Indigenous knowledge and natural infrastructure resilience to climate change in developing countries: a bibliometric analysis - Ebhuoma, Eromose E. (Frontiers in Environmental Economics, 2024)
It is widely recognized that natural infrastructure plays a pivotal role in sustaining Indigenous communities globally. Natural infrastructure encompasses ecosystems and environments that either occur naturally or have been deliberately altered through human intervention to provide multiple benefits for the environment and human wellbeing. While there has been extensive scholarly discussion regarding the importance of natural infrastructure in securing the livelihoods of Indigenous populations in developing nations and passing down their critical knowledge from one generation to another, the literature has not explicitly analyzed how Indigenous knowledge has facilitated the protection and conservation of natural infrastructure. Also, there has been limited analysis of the economic benefits of their conservation efforts. This article, utilizing bibliometric analysis as its methodological approach, aims to unpack how Indigenous knowledge has facilitated the protection and conservation of natural infrastructure. Several key themes emerged from this bibliometric analysis, including Indigenous governance strategies aimed at mitigating deforestation and addressing climate change and collective action taken to preserve natural infrastructure. Among others, a positive economic consequence of all three themes lies in their ability to improve the livelihood of Indigenous peoples by creating opportunities to receive payment for ecosystem services.